2019
DOI: 10.1186/s13063-019-3279-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a programme of vigorous physical activity during secondary school physical education on academic performance, fitness, cognition, mental health and the brain of adolescents (Fit to Study): study protocol for a cluster-randomised trial

Abstract: Background Early adolescence is a period of dynamic neurobiological change. Converging lines of research suggest that regular physical activity (PA) and improved aerobic fitness have the potential to stimulate positive brain changes, improve cognitive function and boost academic attainment in this age group, but high-quality studies are needed to substantiate these findings. The primary aim of the Fit to Study trial is to investigate whether short infusions of vigorous PA (VPA) delivered during se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 89 publications
0
31
0
1
Order By: Relevance
“…The study was a cross-sectional analysis of baseline data from the Fit to Study cluster-randomised controlled trial, registered with ClinicalTrials.gov, NCT03286725. Trial recruitment, methodology and consent procedures are reported elsewhere 26 in line with the Consolidated Standards for Reporting Trials (CONSORT).…”
Section: Methods Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was a cross-sectional analysis of baseline data from the Fit to Study cluster-randomised controlled trial, registered with ClinicalTrials.gov, NCT03286725. Trial recruitment, methodology and consent procedures are reported elsewhere 26 in line with the Consolidated Standards for Reporting Trials (CONSORT).…”
Section: Methods Designmentioning
confidence: 99%
“…49 Cronbach's alpha for the peer, conduct and pro-social subscales of the SDQ was <0.7, in line with evidence that, in community samples, these more focused scales might not reliably capture distinct aspects of mental health. 35 Recommendations for future studies Our design does not support conclusions about causality: the Fit to Study cluster-randomised controlled trial 26 aims to establish causation. Future studies could explore the role of muscular fitness, and measure relationships between mental health and physical activity in different contexts, including leisure time and competition.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…According to the World Health Organization, regular physical activity is an effective way to prevent and treat chronic non-communicable diseases (1) , promote mental health/health (2)(3) and well-being (4)(5) . Spirituality and religiosity also influence an individual's health (6) .…”
Section: Introductionmentioning
confidence: 99%
“…A brain imaging sub-study investigated the underlying neural mechanisms of hypothesized correlations between cardiovascular exercise and cognitive function. Researchers published full details of FtS in the study protocol [11] and the study evaluation report [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers at the University of Oxford and Oxford Brookes designed the intervention, delivered teacher training, and collected secondary measures of fitness, cognitive function, mental health and VPA during PE [11] . NatCen Social Research, the independent evaluator, set the sample size, collected the primary attainment measure, conducted an implementation and process evaluation, and published the primary results [12] .…”
Section: Introductionmentioning
confidence: 99%